Variance-resistant PTB7 and axially-substituted silicon phthalocyanines as active materials for high-Voc organic photovoltaics - Mario C. Vebber (Nature Portfolio, 2021)
Abstract While the efficiency of organic photovoltaics (OPVs) has improved drastically in the past decade, such devices rely on exorbitantly expensive materials that are unfeasible for commercial applications. Moreover, examples of high voltage single-junction devices, which are necessary for several applications, particularly low-power electronics and rechargeable batteries, are lacking in literature. Alternatively, silicon phthalocyanines (R2-SiPc) are inexpensive, industrially scalable organic semiconductors, having a minimal synthetic complexity (SC) index, and are capable of producing high voltages when used as acceptors in OPVs. In the present work, we have developed high voltage OPVs composed of poly({4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b′]dithiophene-2,6-diyl}{3-fluoro-2-[(2-ethylhexyl)carbonyl] thieno [3,4 b]thiophenediyl}) (PTB7) and an SiPc derivative ((3BS)2-SiPc). While changes to the solvent system had a strong effect on performance, interestingly, the PTB7:(3BS)2-SiPc active layer were robust to spin speed, annealing and components ratio. This invariance is a desirable characteristic for industrial production. All PTB7:(3BS)2-SiPc devices produced high open circuit voltages between 1.0 and 1.07 V, while maintaining 80% of the overall efficiency, when compared to their fullerene-based counterpart.